Expanded antigen-experienced CD160+CD8+effector T cells exhibit impaired effector functions in chronic lymphocytic leukemia. Issue 4 (30th April 2021) - Bozorgmehr, Najmeh; Okoye, Isobel; Oyegbami, Olaide; Xu, Lai; Fontaine, Amelie; Cox-Kennett, Nanette; Larratt, Loree M; Hnatiuk, Mark; Fagarasanu, Andrei; Brandwein, Joseph; Peters, Anthea C; Elahi, Shokrollah
Abstract : Background: T cell exhaustion compromises antitumor immunity, and a sustained elevation of co-inhibitory receptors is a hallmark of T cell exhaustion in solid tumors. Similarly, upregulation of co-inhibitory receptors has been reported in T cells in hematological cancers such as chronic lymphocytic leukemia (CLL). However, the role of CD160, a glycosylphosphatidylinositol-anchored protein, as one of these co-inhibitory receptors has been contradictory in T cell function. Therefore, we decided to elucidate how CD160 expression and/or co-expression with other co-inhibitory receptors influence T cell effector functions in patients with CLL. Methods: We studied 56 patients with CLL and 25 age-matched and sex-matched healthy controls in this study. The expression of different co-inhibitory receptors was analyzed in T cells obtained from the peripheral blood or the bone marrow. Also, we quantified the properties of extracellular vesicles (EVs) in the plasma of patients with CLL versus healthy controls. Finally, we measured 29 different cytokines, chemokines or other biomarkers in the plasma specimens of patients with CLL and healthy controls. Results: We found that CD160 was the most upregulated co-inhibitory receptor in patients with CLL. Its expression was associated with an exhausted T cell phenotype. CD160 + CD8 + T cells were highly antigen-experienced/effector T cells, while CD160 + CD4 + T cells were more heterogeneous. In particular, we identified EVs as a source of CD160 in the plasma of patients with CLL that can be taken up by T cells. Moreover, we observed a dominantly proinflammatory cytokine profile in the plasma of patients with CLL. In particular, interleukin-16 (IL-16) was highly elevated and correlated with the advanced clinical stage (Rai). Furthermore, we observed that the incubation of T cells with IL-16 results in the upregulation of CD160. Conclusions: Our study provides a novel insight into the influence of CD160 expression/co-expression with other co-inhibitory receptors in T cell effector functions in patients with CLL. Besides, IL-16-mediated upregulation of CD160 expression in T cells highlights the importance of IL-16/CD160 as potential immunotherapy targets in patients with CLL. Therefore, our findings propose a significant role for CD160 in T cell exhaustion in patients with CLL.